For the place of Barbare Jorjadze In the history of Georgian literary language - Vashakidze, Iamze (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2021)
From the point of view of studying the history of the Georgian literary language, the second half of the XIX century is a very remarkable period, when according to the current anti-Georgian political course in the country, the struggle of the advanced Georgian society to save the literary language intensifies. The battle is led by the generation of 60s inspired by the national spirit, under the leadership of Ilia Chavchavadze. Contrary to the policy of becoming Russian, the leading society begins to focus on the current issues of literary language and writing; in this case, the basement was created by the representatives of the generation of the 50s gathered in the magazine „Tsiskari“, among whom there was the writer and publicist Barbare Jorjadze, to implement main changes in this direction. The aim of the present study is to determine the importance of the individual figures who contributed to the development of the history of the Georgian literary language as a unified continuous process. The controversy with Barbare Jorjadze, besides the fact it rise great interest from the public and made the controversial issues of the language the subject of wide discussion, opened the barriers to Ilia Chavchavadze too perfectly presented his linguistic concept, which is still in the sphere of interest of specialists. Our conclusion is as follows: 1. Barbare Jorjadze is a representative of the generation „brought up at home“ according to the outdated literary norms of Anton Katholikos, who does not have the ability to take into account the developments in the language according to the new era. In contrast, Ilia Chavchavadze, who shares advanced Russian and European ideas and is educated in higher education outside Georgia, has access to general language changes, in general; It is a great service of Ilia Chavchavadze and his generation to establish a unified literary style, remove outdated letters from the alphabet, separation of borrowed words and linguistic mistakes (barbarisms) in the foreign language lexical stream and in general, the solution of all the disputable language issues that were still the subject of public discussion, in the first half of the nineteenth century. 2. Against the background of aforesaid controversy, it is clearly visible a great service of Barbare Jorjadze, a worthy representative of the advanced society of the 50s of XIX century, in the process of creating a literary language: based on the principle of protection of inheritance, the merits of Barbare Jorjadze (as well as her generation) should be appreciated, as a necessary preparatory stage for the language democracy reforms carried out in the 1960s. With such an approach, the history of the creation of written language will be renovated in front of our eyes, as a continuous process; in this process, there are some bibliophiles of the XIX century in the appropriate place, as well as Anton Katholikos and the defenders of his norms, and then - the 60s.